Development of Hybrid Linear Friction Welding of overlap and T joints in aluminum alloys - Maciel, Ricardo; Braga, Daniel F.O.; Infante, Virgínia I. M. N.; Moreira, Pedro M.G.P.; da Silva, Lucas F.M. (Seven Editora, 2023)
While Linear Friction Welding (FSW) has been shown to produce high performance butt joints, stress concentration at the weld edges in the FSW lap significantly reduces the performance of these joints. In this article, the research studies carried out will be presented, referring to the development of the process of joining metals, linear friction welding (FSW) in combination with adhesive bonding (AB), Friction Stir Weld-Bonding (FSWB), for overlapping joints (SLJ) and AA 6082-T6 aluminum alloy T-joints. Before the manufacturing of optimized joints was achieved, it was necessary to carry out several experimental weldings to select the FSW parameters for the lap and T joints. The current article intends to present the results obtained for the different tests carried out, as well as the discussion of these, regarding the improvement of the fatigue strength of lap joints using the FSWB process when compared to the FSW process. FSWB welding achieved a significant increase in quasi-static and fatigue strength when compared to FSW overlay, with 79.9% of the adhesive joint fatigue strength at 106 cycles, while FSW had 41.6%. bending of T-joints in an integral frame configuration will also be presented and discussed. DOI: https://doi.org/10.56238/methofocusinterv1-076